Etika dan Kompetensi Konselor Sebagai Profesional (Suatu Pendekatan Literatur Sistematis) - Happy Karlina Marjo; Darojaturroofi'ah Sodiq (Jurnal Paedagogy, 2022)
The purpose of this study was to describe the ethics and competence of counselors as professionals in providing guidance and counseling services. The research method used is a systematic literature study. This systematic literature review contains explanations and descriptions of theories, findings and research materials obtained from databases of national and international journal providers through the Google Scholar platform, and then analyzed descriptively. The result of this research is that ethics and competencies must be possessed by a counselor as the basis for the profession he adheres to. Counselor education is one way to develop competencies for prospective counselors. The competence of the counselor as an agent for counseling guidance services is stated in government regulation No. 19 of 2005 article 28 paragraph 3, namely: competence as a service agent at the level of primary and secondary education and early childhood education which includes pedagogic competence, personality, professional and social competence. Professional counselors must have a strong determination to be able to help others and have a positive nature to be able to view the counselee as a human being who has different values, religious teachings, cultures and backgrounds.